Strategi Pengembangan Literasi Digital Bagi Siswa di Madrasah Ibtidaiyah Al-Falah III Larangan Luar Pamekasan - Ibniyatus Salihah (Lembaga Einstein College (LEC), 2025)
Digital literacy is one of the activities for students at Madrasah Ibtidaiyah Al-Falah III Larangan Luar Larangan Pamekasan using digital tools such as projectors, laptops, or cellphones, because by studying, we can find out small things about knowledge in everyday life that will happen in the future. The purpose of this study was to determine the strategies used at Madrasah Ibtidaiyah Al-Falah III in developing digital literacy owned by students. The approach used was descriptive qualitative by collecting data through interviews, observations, and documentation. Data analysis in this study included data collection, reduction, presentation, and a conclusion. Data collection in this study used interviews with three main subjects; the reduction was carried out in this study by changing the interview recordings into written text, or interview transcripts; then interviews were conducted to compile narrative descriptions that explain the main findings of the data that had been categorized; and drawing conclusions was done by formulating final conclusions that answer the researcher's questions by providing implications and recommendations from the results of the study. Then the data obtained was analyzed using qualitative methods in order to determine the development of students' digital literacy at Madrasah Ibtidaiyah Al-Falah III Larangan Luar effectively and efficiently. The results of the study showed that digital literacy at Madrasah Ibtidaiyah Al-Falah III was able to compete with outside conditions to be able to hone and improve students' critical abilities regarding how important digital literacy is.